Selective loss of parvalbumin-positive GABAergic interneurons in the cerebral cortex of maternally stressed Gad1-heterozygous mouse offspring - Uchida, T (Nature Publishing Group, 2014)
Exposure to maternal stress (MS) and mutations in GAD1, which encodes the γ-aminobutyric acid (GABA) synthesizing enzyme glutamate decarboxylase (GAD) 67, are both risk factors for psychiatric disorders. However, the relationship between these risk factors remains unclear. Interestingly, the critical period of MS for psychiatric disorders in offspring corresponds to the period of GABAergic neuron neurogenesis and migration in the fetal brain, that is, in the late stage of gestation. Indeed, decrement of parvalbumin (PV)-positive GABAergic interneurons in the medial prefrontal cortex (mPFC) and hippocampus (HIP) has often been observed in schizophrenia patients. In the present study, we used GAD67-green fluorescent protein (GFP) knock-in mice (that is, mice in which the Gad1 gene is heterozygously deleted; GAD67(+/GFP)) that underwent prenatal stress from embryonic day 15.0 to 17.5 and monitored PV-positive GABAergic neurons to address the interaction between Gad1 disruption and stress. Administration of 5-bromo-2-deoxyuridine revealed that neurogenesis of GFP-positive GABAergic neurons, but not cortical plate cells, was significantly diminished in fetal brains during MS. Differential expression of glucocorticoid receptors by different progenitor cell types may underlie this differential outcome. Postnatally, the density of PV-positive, but not PV-negative, GABAergic neurons was significantly decreased in the mPFC, HIP and somatosensory cortex but not in the motor cortex of GAD67(+/GFP) mice. By contrast, these findings were not observed in wild-type (GAD67(+/+)) offspring. These results suggest that prenatal stress, in addition to heterozygous deletion of Gad1, could specifically disturb the proliferation of neurons destined to be PV-positive GABAergic interneurons.